Assessing the effects of trade on employment: An assessment toolkit - Cheong, David (Animo Repository, 2019)
Employment is a key driver for development as it constitutes a bridge between economic growth and poverty reduction. People and households get out of poverty most often by moving into more productive and decent jobs or improving existing jobs. Placing the aim of achieving full and productive employment at the heart of development policy is therefore critical for reducing and eventually eliminating poverty, reducing inequality and addressing informality. This is also now globally recognized with the adoption of Sustainable Development Goal (SDG) 8: “Promote sustained, inclusive and sustainable economic growth, full and productive employment and decent work for all” The European Commission (EC) and the International Labour Organization (ILO) both recognize that, in order to achieve SDG 8, it is critical that full and productive employment be at the heart of development policy. In the “New European Consensus on Development”, the EC emphasizes the importance of targeted policies in developing countries to promote the engagement of citizens - especially the youth, women and potential migrants - in social, civic and economic life and to ensure their full contribution to inclusive growth and sustainable development. International trade has been advocated as a means of achieving sustainable development. Paragraph 79 of the Addis Ababa Action Agenda states that “with appropriate supporting policies, infrastructure and an educated work force, trade can also help to promote productive employment and decent work, women’s empowerment and food security, as well as a reduction in inequality, and contribute to achieving the sustainable development goals”. However, creating more and better-quality jobs through international trade requires a coherent policy framework aimed at generating and upgrading employment. This policy framework should be based on a clear and shared understanding of how trade policy and other policies complementary to trade (e.g., sectoral, skills, infrastructure, investment, exchange rate, etc.) are expected to affect employment. In this regard, the EC and ILO have jointly initiated a project entitled “Strengthening the Impact on Employment of Sectoral and Trade Policies”. This innovative project includes developing methods and capacities to determine the effects of trade and complementary policies on employment. This project, being implemented in nine partner countries and working with national governments and social partners, aims to strengthen the capabilities of country partners to analyse, design and implement sectoral and trade policies and programmes for more and better jobs. This toolkit is one in a series of project publications that aim to capture the tools, methods and processes developed under this project as well as the findings from implementing these in the nine partner countries. By doing so, the experience and learning of the project can be disseminated to other countries and partners for their benefit, thus encouraging the integration of global and national employment objectives into sectoral and trade policies and consequently supporting the global employment agenda and the achievement of SDG 8.